The Praxis of Historical Memory: Pepe Galán’s Memorial - Thompson, John (Madrygal. Revista de Estudios Gallegos, 2019)
Erected since the end of the last century, memorials that symbolize fascist crimes have played a problematic role in the process of recovering historical memory. The large majority of them have been abandoned, hence it is more probable that they work against memory than for it. One exception is Pepe Galán’s work, which is located in a small valley that leads to the little bay of O Portiño, which is part of A Coruña city. The monument alludes to the massacre of a group of leftist militants that attempted to escape from O Portiño in March of 1937. Their intent was to reach Asturias. In order for a memorial as Galan’s to work, great efforts are needed that must come from the asociacións de memoria and from high schools. This monument has never been analyzed despite possessing potential for advancing the cause of historical memory. This situation of abandonment can transform into an opportunity that sensitizes society, especially the youth, to the trauma caused by fascism.